Joe Sacco's Australian Story. Issue 3 (3rd July 2017) - Whitlock, Gillian
ABSTRACT: Although Joe Sacco is frequently present in the frame of his comics journalism, as a witness, listener and scribe, he rarely attaches his own autobiographical experience to these representations of self. Recently some more detailed biographical detail about Joe Sacco's own life story has begun to emerge in the frames of his comics, particularly in his work on refugees and asylum seekers. One of the least significant and little known facts about Joe Sacco's life, his childhood as a migrant in Australia, becomes relevant here, extending his enduring commitment to ethical spectatorship, and the visibility of human rights violations, by engaging with this most difficult and intimate work of interrogating citizenship, our own and 'others'.